Adjacent Lumbar Disc Herniation after Lumbar Short Spinal Fusion - Koshi Ninomiya (Case Reports in Orthopedics, 2014)
A 70-year-old outpatient presented with a chief complaint of sudden left leg motor weakness and sensory disturbance. He had undergone L4/5 posterior interbody fusion with L3–5 posterior fusions for spondylolisthesis 3 years prior, and the screws were removed 1 year later. He has been followed up for 3 years, and there had been no adjacent segment problems before this presentation. Lumbar magnetic resonance imaging (MRI) showed a large L2/3 disc hernia descending to the L3/4 level. Compared to the initial MRI, this hernia occurred in an “intact” disc among multilevel severely degenerated discs. Right leg paresis and bladder dysfunction appeared a few days after admission. Microscopic lumbar disc herniotomy was performed. The right leg motor weakness improved just after the operation, but the moderate left leg motor weakness and difficulty in urination persisted.